The Burden and Impact of Vertigo: Findings from the REVERT Patient Registry - Benecke, Heike; Agus, Sam; Goodall, Gordon; Kuessner, Daniel; Strupp, Michael (Frontiers in Neurology, 2013)
Objective: Despite the high prevalence of vertigo globally and an acknowledged, but underreported, effect on an individual’s wellbeing, few studies have evaluated the burden on healthcare systems and society. This study was aimed to quantitatively determine the impact of vertigo on healthcare resource use and work productivity. Methods: The economic burden of vertigo was assessed through a multi-country, non-interventional, observational registry of vertigo patients: the Registry to Evaluate the Burden of Disease in Vertigo (REVERT). Patients included were those with a new diagnosis of Meniere’s disease (MD), benign paroxysmal positional vertigo (BPPV), other vertigo of peripheral vestibular origin or peripheral vestibular vertigo of unknown origin. Results: A total of 4,294 patients at 618 centers in 13 countries were included during the registry. Of the 4,105 patients analyzed, only half were in employment. Among this working patient population, 69.8% had reduced their workload, 63.3% had lost working days and 4.6% had changed and 5.7% had quit their jobs, due to vertigo symptoms. Use of healthcare services among patients was high. In the 3 months preceding Visit 1, patients used emergency services 0.4 ± 0.9 times, primary care consultations 1.6 ± 1.8 times and specialist consultations 1.4 ± 2.0 times (all mean ± SD). A mean of 2.0 ± 5.4 days/patient was also spent in hospital due to vertigo. Conclusions: In addition to the negative impact on the patient from a humanistic perspective, vertigo has considerable impact on work productivity and healthcare resource use.